2000
DOI: 10.2308/accr.2000.75.3.283
|View full text |Cite
|
Sign up to set email alerts
|

The Balanced Scorecard: Judgmental Effects of Common and Unique Performance Measures

Abstract: The balanced scorecard is a new tool that complements traditional measures of business unit performance. The scorecard contains a diverse set of performance measures, including financial performance, customer relations, internal business processes, and learning and growth. Advocates of the balanced scorecard suggest that each unit in the organization should develop and use its own scorecard, choosing measures that capture the unit's business strategy. Our study examines judgmental effects of the balanced score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
487
1
34

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(543 citation statements)
references
References 9 publications
21
487
1
34
Order By: Relevance
“…Similar to other accounting studies (e.g., Maiga and Jacobs, 2003;Hendricks et al, 2004;Braam and Nijssen, 2004), we found no evidence that the use of BSC as a performance measurement system enables managers to learn more effectively about the business system and improve its performance. Consistent with Lipe and Salterio (2000), this research also suggests that, due to cognitive limitations, managers may not appreciate the significance of non-financial and leading measures, thereby sidestepping the cause-and-effect logic chain and reducing the potential benefits of using the BSC. BSC usage only leads to higher performance if managers understand the cause-and-effect relations that link drivers with future financial performance.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Similar to other accounting studies (e.g., Maiga and Jacobs, 2003;Hendricks et al, 2004;Braam and Nijssen, 2004), we found no evidence that the use of BSC as a performance measurement system enables managers to learn more effectively about the business system and improve its performance. Consistent with Lipe and Salterio (2000), this research also suggests that, due to cognitive limitations, managers may not appreciate the significance of non-financial and leading measures, thereby sidestepping the cause-and-effect logic chain and reducing the potential benefits of using the BSC. BSC usage only leads to higher performance if managers understand the cause-and-effect relations that link drivers with future financial performance.…”
Section: Resultssupporting
confidence: 59%
“…There exist studies in the field of management accounting research that identify problems and limitations associated with the BSC approach. The inadequate definition and utilization of the performance indicators have been highlighted as a main drawback of the BSC system (Lingle and Schiemann, 1996;Stivers et al, 1998;Ittner and Larcker, 1998;Lipe and Salterio, 2000;Malmi, 2001;Speckbacher et al, 2003). Those studies show in general terms that the measures and perspectives in use are fairly independent, and do not always mirror the recommended cause-and-effect logic of the BSC approach.…”
Section: Balanced Scorecard and Organizational Performancementioning
confidence: 98%
See 1 more Smart Citation
“…2 Recent management control research addresses specific factors that might explain firms' choices of performance measures to achieve and maintain strategic advantages. Laboratory experiments (e.g., Libby et al, 2002;Lipe & Salterio, 2000;Luft & Shields, 2001, 2002a and surveys of management control practice (e.g., Cavaluzzo & Ittner, 2002;Ittner & Larcker, 1998) have identified attributes of performance measures that are…”
Section: Performance-measure Attributesmentioning
confidence: 99%
“…This finding was repeated in a recent controlled study involving MBA students who evaluated two divisions of a clothing firm by means of the Balanced Scorecard. Experimental participants evaluated performance solely on the common measures (Lipe & Salterio, 2000). In view of this finding, emphasis on evaluation of both common and unique behavioural variables was stimulated by increasing understanding of non-traditional measures.…”
Section: Methods Samplementioning
confidence: 99%